2019
DOI: 10.1021/acssensors.9b00175
|View full text |Cite|
|
Sign up to set email alerts
|

Development of Label-Free Colorimetric Assay for MERS-CoV Using Gold Nanoparticles

Abstract: Worldwide outbreaks of infectious diseases necessitate the development of rapid and accurate diagnostic methods. Colorimetric assays are a representative tool to simply identify the target molecules in specimens through color changes of an indicator (e.g., nanosized metallic particle, and dye molecules). The detection method is used to confirm the presence of biomarkers visually and measure absorbance of the colored compounds at a specific wavelength. In this study, we propose a colorimetric assay based on an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
147
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(148 citation statements)
references
References 35 publications
0
147
0
1
Order By: Relevance
“…The fight against infectious diseases caused by viruses remains a challenging and endless task despite the tremendous efforts and significant advances in public healthcare. Infectious diseases pose a significant risk to human health and have led to approximately onefourth of deaths worldwide [1,2]. Coronaviruses belong to the family of Coronaviridae and may cause respiratory and neurological diseases [3].…”
Section: Introductionmentioning
confidence: 99%
“…The fight against infectious diseases caused by viruses remains a challenging and endless task despite the tremendous efforts and significant advances in public healthcare. Infectious diseases pose a significant risk to human health and have led to approximately onefourth of deaths worldwide [1,2]. Coronaviruses belong to the family of Coronaviridae and may cause respiratory and neurological diseases [3].…”
Section: Introductionmentioning
confidence: 99%
“…Free or immobilized DNA probes were tagged with transducing elements in advance or become subjected to them after hybridizing with the targets. Electrochemical [100][101][102][103] and optical agents [24,37,77,[104][105][106] are examples of transducers that have been employed in these gene-based sensors to produce measurable signals corresponding to the presence or absence of viral RNA. Figure 5 presents a schematic of the principle underlying of these biosensors.…”
Section: Biosensors For Viral Rna Detectionmentioning
confidence: 99%
“…In this regard, Kim et al recently reported colorimetric trials to identify targeted biomolecules through LSPR shifts and color changes in spherical AuNP suspensions by selecting a target and a control upstream of the E protein gene (upE) and open reading frames (ORF) 1a of MERS-CoV and tobacco mosaic virus (TMV), respectively [ 218 ]. This is based on the interaction of the negatively charged citrate ion-capped AuNPs with disulfides, salts and targeted probes.…”
Section: Diagnostics and Biosensors For Covid-19mentioning
confidence: 99%